Climate Change Adaptation, Livelihoods and Resilience Interface, A Meta-Analysis - Acharya, Ganesh Raj; Tiwari, Krishna Raj; Acharya, Sanjaya (Himalayan Biodiversity, 2025)
The paper explores the interface study of adaptation, resilience and livelihoods in climate and development context. Climate change is emerging as an important developmental challenge globally and in Nepal. Discourse of climate change is mostly attributed to the adverse effect to community and their livelihoods. This paper intends to explore relation among the adaptation, livelihoods and resilience in an interface. Both quantitative and qualitative approach is adapted. With the set criteria, the review of 75 papers was carried for meta-study. Codes were developed based on review. The framing and argumentation elaborated the code. The study explores that adaptation contributes to livelihoods, quality living and decreases vulnerability to climate change with increased resilience. Similarly, the increased livelihoods complement the adaptation. The resilience is the capacity for successful adaptation, ability to respond, recover and the capacity of a system to absorb disturbance and reorganize during undergoing change. The framing and argumentation of adaptation, livelihoods and resilience reviewed contribute one another. The correlation also shows that there is high degree of positive correlation between adaptation and resilience (0.433). The relation between livelihoods and adaptation is in lowest (0.133) where that of resilience and livelihoods is in between (0.300). Adaptation and livelihoods are interconnected and so is the adaptation and resilience; livelihoods and resilience. The study of climate change adaptation, livelihoods and resilience is a dynamic concept. This study has generated interface knowledge about resilience, adaptation and livelihoods approaches making the existing knowledge gap on this interface narrower.